The Drosophila Su(var)3–7 Gene Is Required for Oogenesis and Female Fertility, Genetically Interacts with piwi and aubergine, but Impacts Only Weakly Transposon Silencing - Basquin, Denis (Public Library of Science, 2014)
Heterochromatin is made of repetitive sequences, mainly transposable elements (TEs), the regulation of which is critical for genome stability. We have analyzed the role of the heterochromatin-associated Su(var)3–7 protein in Drosophila ovaries. We present evidences that Su(var)3–7 is required for correct oogenesis and female fertility. It accumulates in heterochromatic domains of ovarian germline and somatic cells nuclei, where it co-localizes with HP1. Homozygous mutant females display ovaries with frequent degenerating egg-chambers. Absence of Su(var)3–7 in embryos leads to defects in meiosis and first mitotic divisions due to chromatin fragmentation or chromosome loss, showing that Su(var)3–7 is required for genome integrity. Females homozygous for Su(var)3–7 mutations strongly impair repression of P-transposable element induced gonadal dysgenesis but have minor effects on other TEs. Su(var)3–7 mutations reduce piRNA cluster transcription and slightly impact ovarian piRNA production. However, this modest piRNA reduction does not correlate with transposon de-silencing, suggesting that the moderate effect of Su(var)3–7 on some TE repression is not linked to piRNA production. Strikingly, Su(var)3–7 genetically interacts with the piwi and aubergine genes, key components of the piRNA pathway, by strongly impacting female fertility without impairing transposon silencing. These results lead us to propose that the interaction between Su(var)3–7 and piwi or aubergine controls important developmental processes independently of transposon silencing.